A2_9 None Like It Hot - Clapton, Simon; Meredith, Calum; Boulderstone, David (Physics Special Topics, 2011)
This paper looks into the use of a Hohmann transfer to help combat global warming by moving the Earth further away from the Sun to reduce its surface temperature. It was found that the total delta-v required to move the Earth from its current orbit to one which would lower the temperature by 1.1 oC, would be 117.5 ms-1.